2,3 : 5,6-Di-O-isopropylidene-3,5-di-C-methyl-L-mannono-1,4-lactone - Booth, K; Jenkinson, S; Fleet, G; Watkin, D (2007)
The relative configuration at C-2 of the title lactone, C14H22O6, which exists in the five-membered ring form, was unequivocally established by X-ray crystallographic analysis. The absolute configuration was determined by the use of 2,4-di-C-methyl-l-arabinose as the starting material. © 2007 International Union of Crystallography. All rights reserved.